Important Medicinal Plant Families in Thailand - Phumthum, Methee; Balslev, Henrik; Barfod, Anders S. (Frontiers in Pharmacology, 2019)
Throughout the world surveys have been conducted at the country level to answer research questions pertaining to ethnomedicinal usage patterns. This study is focused on Thailand, which has never been surveyed systematically in this way. We mined 16,000 use reports from 64 scientific reports, published from 1990 to 2014. In total, 2187 plant species were cited as being useful for medicinal purposes. The overall aim was to reveal the relative importance of the plant families for pharmacological research. To determine the most important medicinal plant families we use a combination of three statistical approaches: linear regression, Binomial analysis and Bayesian analysis. At the regional level 19 plant families repeatedly stood out as being the most important from an ethnomedicinal perspective.